Exenatide Is an Effective Antihyperglycaemic Agent in a Mouse Model of Wolfram Syndrome 1. (16th March 2016) - Sedman, Tuuli; Rünkorg, Kertu; Krass, Maarja; Luuk, Hendrik; Plaas, Mario; Vasar, Eero; Volke, Vallo
Abstract : Wolfram syndrome 1 is a very rare monogenic disease resulting in a complex of disorders including diabetes mellitus. Up to now, insulin has been used to treat these patients. Some of the monogenic forms of diabetes respond preferentially to sulphonylurea preparations. The aim of the current study was to elucidate whether exenatide, a GLP-1 receptor agonist, and glipizide, a sulphonylurea, are effective in a mouse model of Wolfram syndrome 1. Wolframin-deficient mice were used to test the effect of insulin secretagogues. Wolframin-deficient mice had nearly normal fasting glucose levels but developed hyperglycaemia after glucose challenge. Exenatide in a dose of 10 μ g/kg lowered the blood glucose level in both wild-type and wolframin-deficient mice when administered during a nonfasted state and during the intraperitoneal glucose tolerance test. Glipizide (0.6 or 2 mg/kg) was not able to reduce the glucose level in wolframin-deficient animals. In contrast to other groups, wolframin-deficient mice had a lower insulin-to-glucose ratio during the intraperitoneal glucose tolerance test, indicating impaired insulin secretion. Exenatide increased the insulin-to-glucose ratio irrespective of genotype, demonstrating the ability to correct the impaired insulin secretion caused by wolframin deficiency. We conclude that GLP-1 agonists may have potential in the treatment of Wolfram syndrome-related diabetes.